Introducing GitHub a non-technical guide - Bell, Peter; Beer, Brent (O'Reilly Media, 2015)
If you're new to GitHub, this concise book shows you just what you need to get started and no more. It's perfect for project and product managers, stakeholders, and other team members who want to collaborate on a development project-whether it's to review and comment on work in progress or to contribute specific changes. It's also great for developers just learning GitHub. This hands-on book shows you how to use GitHub's web interface to view projects and collaborate effectively with your team.